2015
DOI: 10.1051/epjconf/20159401076
|View full text |Cite
|
Sign up to set email alerts
|

Study of phase transitions in cerium in shock-wave experiments

Abstract: Abstract. Cerium has a complex phase diagram that is explained by the presence of structure phase transitions. Planar gauges were used in various combinations in experiments for determination of sound velocity dependence on pressure in cerium by the technique of PVDF gauge. The data of time dependence on pressure profiles with use of x(t) diagrams and the D(u) relation for cerium allowed the definition of the Lagrangian velocity of the unloading wave C Lagr and the Eulerian velocity C Eul by taking into accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Recently, Hixson et al [40] measured the shock temperature, stress and dynamic emissivity of Ce shocked from 8.4 to 23.5 GPa, and found that the samples were shocked from the γ into α phase when the shock stress is below 10.24 GPa. Zhernokletov et al [41] determined the γ→α PT pressure as 0.83 ± 0.06 GPa among a number of shock wave tests ranging up to 3 GPa. The above review of reported experiments thus indicate that the more shock wave experiments are needed to provide enough data for constructing a multiphase EOS of Ce.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Hixson et al [40] measured the shock temperature, stress and dynamic emissivity of Ce shocked from 8.4 to 23.5 GPa, and found that the samples were shocked from the γ into α phase when the shock stress is below 10.24 GPa. Zhernokletov et al [41] determined the γ→α PT pressure as 0.83 ± 0.06 GPa among a number of shock wave tests ranging up to 3 GPa. The above review of reported experiments thus indicate that the more shock wave experiments are needed to provide enough data for constructing a multiphase EOS of Ce.…”
Section: Introductionmentioning
confidence: 99%